ChemInform Abstract: Synthesis and Photoluminescence Properties of Ba2GeO4:Mn4+ Novel Deep Red‐Emitting Phosphor. Issue 9 (February 2016) - Cao, Renping; Luo, Wenjie; Xiong, Qingqiang; Jiang, Shenhua; Luo, Zhiyang; Fu, Jingwei
Abstract: The title phosphor is synthesized by solid state reaction of BaCO3, GeO2, and MnCO3 (air; 1.